The Lived Experience of Pediatric Gene Therapy: A Scoping Review - Kimberly, Laura; Hunt, Cara; Beaverson, Katherine; James, Emma; Bateman-House, Alison; McGowan, Richard; DeSante-Bertkau, Jennifer (Human gene therapy, 2023)
Little is known about patients' and families' lived experiences of participating in pediatric gene therapy (GT) clinical trials. Currently, pediatric GT research targets a broad range of indications--including rare and ultra-rare diseases--which vary in severity and in the availability of alternative therapies. Pediatric GT differs meaningfully from adult GT because the decision to participate involves a dyad of both the child and parent or caregiver/s. It is critical to understand patients' and caregivers' perceptions and experiences of social, emotional, physical, and logistical burdens or benefits of participating in such trials, and how they weigh and prioritize these factors when deciding whether to participate. We conducted a scoping review of the current literature in this subject area with objectives to (1) provide an overview of existing literature, (2) identify gaps and areas for further research, and (3) better understand the lived impact of pediatric GT research on patients and their parents/caregivers. Four themes emerged, including (1) weighing risks and benefits (2) timing of GT trial participation, (3) value of clear communication, and (4) potential impact on quality of life. Notably, our sample surfaced articles about how patients/parents/caregivers about GT-their understanding of its safety, efficacy, and risks-rather than accounts of their , which was our initial intention. Nevertheless, our findings offer useful insights to improve the informed consent process and promote a more patient- and family-centered approach. Moreover, our findings can contribute to patient advocacy organizations' efforts to develop educational materials tailored to patients' and families' expressed informational needs and perspectives, and can inform more patient- and family-centered policies from GT clinical trial sponsors.